2016
DOI: 10.1038/sc.2016.114
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes 2 years after traumatic spinal cord injury in Botswana: a follow-up study

Abstract: Despite high rates of UTIs and PUs developed in the home environment, this study showed a high survival rate 2 years after traumatic SCI, which might be explained by the establishment of a specialised SCI unit and the high follow-up rate. In addition, the continuing contact with the SCI staff might have facilitated the relatively high return-to-work rate. Long-term follow-up seems possible even in resource-constrained settings with clearly stated objectives, transport, dedicated staff and well-educated patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Only 15% of participants reported muscle spasms as a moderate or chronic problem even though this was the most commonly reported problem on the SCI-SCS. This is a lower rate of complications than reported in comparable studies from LMICs [5,26,27] and even lower than reported from HICs [3,7,[28][29][30]. Similarly, none of the participants in our cohort reported injuries secondary to loss of sensation even though others have found that up to 50% of participants experience this complication [29,30].…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Only 15% of participants reported muscle spasms as a moderate or chronic problem even though this was the most commonly reported problem on the SCI-SCS. This is a lower rate of complications than reported in comparable studies from LMICs [5,26,27] and even lower than reported from HICs [3,7,[28][29][30]. Similarly, none of the participants in our cohort reported injuries secondary to loss of sensation even though others have found that up to 50% of participants experience this complication [29,30].…”
Section: Discussionsupporting
confidence: 45%
“…All but one participant with a pressure ulcer used a wheelchair for mobility at discharge. These findings probably underestimate the real problems that pressure ulcers pose in LMICs [7,25,26] because those who had already died (n = 81) or were not interviewed for other reasons (n = 4) may have been more likely to have experienced pressure ulcers had they been alive and included [13,14]. Our findings may also not be reflective of the severity of the problem for most people living with SCI in LMICs because the participants in our cohort may have been better able to manage skin problems than most.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The author(s) declared no potential conflicts of interest with respect to the research, authorship, and/or publication of this article. .303 21 24 .591 7 (6-12) 8 (7)(8)(9)(10)(11)(12)(13)(14) .193 33 40 .277…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…Despite improvements in TSI management, resource-constrained settings have not yet benefitted from this progress to the same extent as more developed countries. [6][7][8] Although neurosurgery has been developing in East Africa since the 1940s, it remains tertiary and expensive. 9 Both stabilization techniques and time to surgery for spinal trauma are largely unreported.…”
Section: Introductionmentioning
confidence: 99%